PENGARUH RASIO LIKUIDITAS DAN PROFITABILITAS TERHADAP LABA PERUSAHAAN - Ade Rias Okiana; Rawidjo Rawidjo (STIE Muhammadiyah Jakarta, 2020)
The purpose of this study is to determine whether there is an influence of current ratio, profit margin, return on assets to company profits at PT. Dharma Satya Nusantara. The type of data in this study is secondary data which is quantitative data in the form of nominal figures from the company studied in the form of financial statements of PT. Dharma Satya Nusantara in 2013-2016. Testing the hypothesis in this study using multiple linear regression. T test results indicate that Current Ratio and Profit Margin have no significant effect on earnings, while Return On Assets significantly influence earnings. The results of the analysis of the F test and the Determinant Coefficient (R²) test show that the current ratio, profit margin, return on assets significantly influence company profits.